New Driving Structure to Increase Pixel Charging Ratio for UHD TFT-LCDs With High Frame Rate - Chih-Lung Lin; Jui-Hung Chang; Fu-Hsing Chen; Po-Cheng Lai; Yi-Chien Chen; Cheng-Han Ke; Chia-En Wu; Jia-Tian Peng (IEEE Access)
This paper proposes a new driving structure of the thin-film transistor liquid crystal display (TFT-LCD) that can yield a high image quality with a reduction in the number of source driver ICs for use in narrow-bezel notebook displays with ultra-high definition (UHD) and a high frame rate. The proposed driving structure improves the pixel charging ratio by reducing the RC loadings of TFTs of de-multiplexers on data lines and extending the available row-line time for pixel charging. A new gate driver circuit that generates two output waveforms in a single stage is presented to reduce the cost and occupied layout area of gate driver ICs, enabling the realization of high-resolution displays with a narrow bezel. To verify the feasibility of the proposed driving structure, a 12.3-inch panel with UHD (3840 × 2160) and a frame rate of 120 Hz is fabricated. Experimental results demonstrate that the proposed driving structure yields a measured pixel charging ratio of more than 97.09% for a heavy loading pattern with a gray level of 255. Following an accelerated lifetime test, the measured waveforms of the proposed gate driver circuit are stable without any malfunction, demonstrating its high reliability. Therefore, the proposed driving structure and the gate driver circuit are highly suitable for use in UHD TFT-LCD notebook applications.